Calanthe tsiana, a new orchid species from China (Epidendroideae: Collabieae): evidence from morphological and molecular analyses - Chen, Yan-Qiong; Zhu, Ya-Ting; Zhong, Hui; Li, Ze-Xin; Liu, Zhong-Jian; Zhai, Jun-Wen; Lan, Si-Ren (Phytotaxa, 2020)
A new orchid, Calanthe tsiana, is described from southeastern Yunnan, China, based on morphological and DNA evidence. In morphological comparisons, C. tsiana is similar to C. arisanensis, but it differs in having subspatulate petals and falcate-obovate lateral lobes of lip with one ridge on the disk. The phylogenetic analyses based on nuclear ribosomal ITS and plastid DNA (rbcL, matK and trnL-trnF) place C. tsiana with C. arisanensis as sister species and support C. tsiana as a new species.